Well-being after severe brain injury: What counts as good recovery? - Graham, M; Naci, L (Cambridge University Press, 2021)
Disorders of consciousness (DOC) continue to profoundly challenge both families and medical professionals. Once a brain-injured patient has been stabilized, questions turn to the prospect of recovery. However, what “recovery” means in the context of patients with prolonged DOC is not always clear. Failure to recognize potential differences of interpretation—and the assumptions about the relationship between health and well-being that underlie these differences—can inhibit communication between surrogate decisionmakers and a patient’s clinical team, and make it difficult to establish the goals of care. The authors examine the relationship between health and well-being as it pertains to patients with prolonged DOC. They argue that changes in awareness or other function should not be equated to changes in well-being, in the absence of a clear understanding of the constituents of well-being for that particular patient. The authors further maintain that a comprehensive conception of recovery for patients with prolonged DOC should incorporate aspects of both experienced well-being and evaluative well-being.